Health education based on precede-proceed model in perioperative functional exercise for patients with lung cancer (基于格林模式的健康教育在肺癌患者围手术期功能锻炼中应用) - CAI Daoling (蔡道玲) (中西医结合护理)
Objective To investigate the application effect of health education based on precede-proceed model in perioperative functional exercise for patients with lung cancer. Methods Totally 104 patients undergoing video-assisted thoracoscopic resection for lung cancer were randomly divided into the observation group and control group, with 52 cases in each group. All patients received routine care and health education, and the precede-proceed model was used in health education about perioperative functional exercise in the observation group. The compliance with functional exercise, level of knowledge about lung cancer and quality of life after surgery were evaluated and compared between two groups. Results The score of Functional Exercise Compliance Assessment Scale in the observation group was higher than that in the control group after intervention (P＜0. 01). Patients in the observation group were more knowledgeable about lung cancer disease compared with those in the control group (Z=-3. 498, P＜0. 01). Patients in the observation group had higher score of Functional Assessment of Cancer Therapy-Lung (FACT-L) and dimensional score of lung cancer specific module after intervention compared with those in the control group (P＜0. 01). Conclusion Health education based on precede-proceed model is effective to improve the functional exercise compliance, disease awareness and postoperative quality of life in patients with lung cancer. (目的 探讨基于格林模式的健康教育在肺癌患者围手术期功能锻炼中应用的效果。方法 选择104例行电视胸腔镜下肺癌根治术的肺癌患者为研究对象, 随机分为观察组和对照组, 各52例。对照组实施常规健康教育, 观察组在常规护理的基础上应用格林模式进行健康教育。比较两组患者功能锻炼依从性评分、出院前肺癌疾病相关知识的掌握程度和术后生活质量。结果 干预后, 观察组患者功能锻炼依从性量表总分高于对照组, 差异有统计学意义(P＜0. 01)。出院前, 观察组患者肺癌疾病相关知识掌握程度优于对照组, 差异有统计学意义(Z=-3. 498, P＜0. 01)。干预后, 观察组FACT-L量表总分和肺癌特异性模块维度评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 基于格林模式的健康教育有助于提高肺癌患者围手术期功能锻炼依从性, 改善患者对自身疾病的认识, 有利于改善术后生活质量。)